Appréciation des risques de contamination microbienne de la viande de petits ruminants dans les abattoirs et dibiteries de Dakar, Senegal - Yougbaré, B. (Ecole Inter Etats des Sciences et Medecine Veterinaires de Dakar, 2014)
In Senegal, the red meat is considered as a first choice food because of its nutritional value. Its value in proteins and its nature made it an indispensable food for a well-proportioned food intake. This sector of activity is very worthy and has permitted the development of others activities like butchering and restaurants commonly called 'dibiteries'. In these dibiteries, meat is served to clients after many manipulations and a wood fire grilling process. However, despites its nutritional qualities, this meat is a favorable environment of bacterial proliferation. People working in slaughter-houses and dibiteries ignored hygienic practices and so contributed to the dissemination and the multiplication of pathogen germs during the production and commercialization process and by affecting the microbiological quality of this meat. This contamination can cause alimentary toxi-infections to consumers. The general objective of this study is to analyze the contamination risks of small ruminants meat produced within slaughterhouses and sold in dibiteries of Dakar. To do so, risk analysis of contamination of the meat in slaughterhouses and dibiteries has been done following the OIE method. A transversal survey conducted in slaughterhouses, slaughter areas and dibiteries of Dakar has permitted to get informations about the quality of the meat from the slaughter to consumption. Questionnaires have been completed and samples of meat have been tested to evaluate the number of germs responsible of the contamination. Thereby, 138 samples of meat (crude and grilled) have been analyzed to search for fecal coliforms, Escherichia coli, Staphylococcus aureus, sulfite-reducing anaerobic agents and total aerobic mesophilic flora. The contamination in slaughterhouses and in slaughter areas has shown an acceptable level for faecal coliforms, E. coli and mesophilic flora but has been satisfactory for sulfite-reducing anaerobic agents and Staphylococcus. Concerning data collected from dibiteries, 20/40 are unsatisfactory for the fecal coliforms, 18/40 for E. coli and 20/40 for the mesophile flora. Sulfite-reducing anaerobic agents were to be neglected. The assessment of the risk has taken into account the factual paths integrating all kind of steps occurring in any bacterial contamination of the meat within slaughterhouses or felling areas, during the transportation, preparation within dibiteries and the consequences that result from that. So, three levels of risks for the consumers have been determined: (i) From enough high to very high (50.52%), (ii) From very weak to a bit high (48.95%) and (iii) Quasi-nil to extremely weak (0.52%) These results allowed us to formulate some prescriptions to the different actors for the improvement of the quality of meat produced within slaughterhouses and sold in dibiteries.